Effects of potassium lactate on sensory attributes, bacterial community succession and biogenic amines formation in Rugao ham - Renyong Liao; Ying Wang; Qiang Xia; Changyu Zhou; Fang Geng; Daodong Pan; Jinxuan Cao (Food Science and Human Wellness)
To deepen the understanding in the effect of potassium lactate on the sensory quality and safety of Rugao ham, sensory attributes, physicochemical parameters, total volatile basic nitrogen (TVBN), microorganism community and biogenic amines of Rugao ham manufactured with different potassium lactate levels (0 %, 0.5 %, 1 %, 2 %) were investigated; the relationship between microbial community and the formation of TVBN and biogenic amines was further evaluated. With the increase of potassium lactate from 0 % to 2 %, the increased sensory scores and the decreased total aerobic bacterial count and TVBN were observed; the abundance of Staphylococcus increased, while the content of Halomonas decreased. LDA effect size (LEfSe) and correlations analysis showed that Staphylococcus equorum and Lactobacillus fermentum could be the key species to improve sensory scores and decrease biogenic amines and TVBN. Metabolic pathway analysis further showed that amino acids metabolism and nitrogen metabolism were mainly involved in decreasing TVBN and biogenic amines in the treatment of 2 % potassium lactate.